Antibacterial breathable yarn and antibacterial breathable socks thereof
Through the design of modified chitosan zinc oxide, the complex function of chitosan cinnamaldehyde Schiff base and silane modified zinc oxide is solved, and the problem of insufficient antibacterial and breathable performance of the yarn is achieved, which is efficient antibacterial and breathable, and is suitable for multi-scenario applications.
Patent Information
- Application Number
- CN202411956011.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-28
AI Technical Summary
The existing yarns have shortcomings in antibacterial and breathable properties, and it is difficult to balance the two in material design, resulting in a decrease in breathable performance when the antibacterial effect is improved, and the uniform distribution of antibacterial components in the material and long-term stability are difficult to control.
The design of modified chitosan zinc oxide is adopted to achieve synergistic effects between multi-component materials by modifying zinc oxide through the complexation of chitosan cinnamaldehyde Schiff base and silane, and enhance antibacterial and breathable properties.
The antibacterial and breathable properties of the antibacterial breathable yarn are significantly optimized, so that it can show long-lasting antibacterial effects and good breathable performance in multiple scenarios, solving the problem that it is difficult to take into account both antibacterial and breathable performance in traditional materials.
Smart Images

Figure CN119736740A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of textile materials, and in particular to an antibacterial breathable yarn and an antibacterial breathable socks thereof. Background Art
[0002] As people's demand for quality of life and health continues to improve, the functional requirements of textiles are gradually developing towards diversification and high performance. In daily life, as a textile that comes into contact with the skin for a long time, the comfort and hygiene of socks are particularly important. Especially in sports, outdoor activities and long-term wear scenarios, the antibacterial and breathable properties of socks have become the core performance indicators that consumers pay attention to. On the one hand, the accumulation of sweat and skin secretions can easily provide a breeding ground for bacteria, causing odor to grow and even cause skin infections. Therefore, socks are required to have lasting antibacterial properties to inhibit bacterial reproduction; on the other hand, the breathability of socks directly affects the comfort of wearing and the ability to discharge moisture, which can effectively reduce moisture accumulation in the feet, reduce discomfort and extend the wearing life. In addition, these performance requirements must also take into account the adaptability of socks in different scenarios, such as the antibacterial effect in high humidity environments, the maintenance of breathability after long-term wear, and the durability after multiple washings. Therefore, developing a yarn and sock material with excellent antibacterial properties and high breathability can not only significantly improve the functionality and comfort of textiles, but also promote the development of the textile industry towards health and high value-added, and has important application value and development prospects in sports, medical care, daily wear and other fields.
[0003] At present, some functional yarns and socks products on the market have attempted to improve antibacterial or breathable properties through modified materials, but there are still significant deficiencies in practical applications. For example, the Chinese patent with publication number CN104611798A discloses a yarn, which is blended with wool and tree fiber, and has breathable properties such as fast absorption and dissipation of moisture, but does not involve antibacterial design, which limits its practical application range. In addition, the Chinese patent with publication number CN107299437A proposes an antibacterial yarn, in which quaternary ammonium salts are used in the yarn to improve the yarn structure by optimizing the weaving process to improve breathability, but the antibacterial demand in the long-term use of the yarn is not solved, and it is difficult to meet the multifunctional performance requirements under high humidity or special environments. The root of these problems is that the existing technology often cannot take into account the balance between antibacterial and breathable properties in material design, and the improvement of antibacterial effect is usually at the expense of breathable properties. At the same time, there is a lack of effective control of the uniform distribution and long-term stability of antibacterial components in the material, resulting in faster performance decay in actual use. To this end, there is an urgent need for an innovatively designed yarn material that has both excellent antibacterial properties and high breathability to meet consumers' increasingly diverse functional demands for textiles and promote the application of functional yarns in a wider range of scenarios. Summary of the invention
[0004] The purpose of the present invention is to provide an antibacterial breathable yarn and a preparation process to solve the problem that the current yarn has insufficient antibacterial and breathable properties.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] An antibacterial breathable yarn, wherein the antibacterial breathable yarn is obtained by spinning polyester fiber, nylon fiber, cotton fiber and elastic fiber;
[0007] The mass ratio of the polyester fiber, nylon fiber, cotton fiber and elastic fiber is (40-60):(20-30):(10-20):(5-10);
[0008] The polyester fiber is prepared from the following components in parts by weight: 85-90 parts of polyethylene terephthalate chips, 3.0-5.0 parts of modified chitosan zinc oxide, 0.3-0.5 parts of antioxidant 1010, 1.0-2.0 parts of POE elastomer, 2.0-3.0 parts of polyether modified silicone oil, and 1.0-2.0 parts of polyethylene glycol 200;
[0009] The modified chitosan zinc oxide is prepared by combining chitosan cinnamaldehyde Schiff base and silane-modified zinc oxide;
[0010] The chitosan cinnamaldehyde Schiff base is obtained by a Schiff base condensation reaction of chitosan and cinnamaldehyde in acetic acid and anhydrous ethanol medium;
[0011] The silane-modified zinc oxide is isocyanatepropyltriethoxysilane-modified nanorod-shaped zinc oxide particles;
[0012] Further, the preparation method of the modified chitosan zinc oxide is as follows: by weight, 10.0-15.0 parts of chitosan cinnamaldehyde Schiff base are added to 500-600 parts of deionized water, and then the pH of the mixed solution is adjusted to 3.0-4.0 with a 3.0wt.% acetic acid solution, and after the adjustment, the solution is stirred at 60-70°C at a stirring rate of 200-250rpm for 20-30min, and then 40.0-50.0 parts of silane-modified zinc oxide are added to the solution, and the mixed solution is placed in an ultrasonic The device is first ultrasonicated for 20 to 30 minutes, then stirred for 30 to 45 minutes in a water bath at 50 to 60° C., and after the stirring is completed, the pH of the mixed solution is adjusted to 8.8 to 9.2 with a 5wt.% sodium hydroxide solution. After the adjustment is completed, a flocculent precipitate is formed in the mixed solution, and then the mixed solution is filtered and the precipitate is retained, and the precipitate is washed 3 times with deionized water. After the washing is completed, it is dried in a vacuum drying oven at 50 to 60° C. for 8 to 12 hours, and the dried product is ground to a particle size of 200 meshes to obtain modified chitosan zinc oxide.
[0013] Further, the preparation method of the silane-modified zinc oxide is as follows: by weight, 15.0-20.0 parts of ethyl glycolate and 40.0-50.0 parts of isocyanatepropyl triethoxysilane are added to a beaker, and 0.20-0.40 parts of dibutyltin dilaurate are added, and stirred at 40.0-45.0° C. and a stirring rate of 300-350 rpm for 200-240 min to form a uniform mixed solution, and then 100-150 parts of nanorod-shaped zinc oxide particles, 200-250 parts of anhydrous ethanol and 150 parts of ethanol are added to the mixed solution in sequence. ~160 parts of deionized water are added thereto, and then the mixed solution is ultrasonicated for 30~45 minutes. After the ultrasonic treatment is completed, the pH value of the solution is adjusted to 9.8~10.2 with a 5wt.% sodium hydroxide solution. After the pH is adjusted, the mixed solution is stirred in a water area of 60~65℃ at a stirring rate of 300~400rpm for 240~300min. After the stirring is completed, the mixed solution is filtered and the precipitate is retained. Then, the precipitate is washed alternately with deionized water and anhydrous ethanol for 3~5 times, and the washed precipitate is dried at 50~60℃ for 6~10h to obtain silane-modified zinc oxide.
[0014] Further, the preparation method of the chitosan cinnamaldehyde Schiff base is as follows: by weight, 10.0-15.0 parts of chitosan are dissolved in 100-120 parts of 1wt.% acetic acid solution to obtain a chitosan solution, and 7.0-10.0 parts of cinnamaldehyde are dissolved in 300-400 parts of anhydrous ethanol to obtain a cinnamaldehyde solution, and then the cinnamaldehyde solution is added dropwise to the chitosan solution. After the dropwise addition is completed, the mixed solution is placed in an oil bath at 40-50°C and stirred at a speed of 350-400 rpm. The mixture was stirred at a high rate for 300 to 360 minutes. After the stirring was completed, a 5 wt.% sodium hydroxide solution was slowly added dropwise to the solution, and the pH of the solution was adjusted to 10 until a flocculent precipitate was formed in the solution. The mixed solution was then filtered and the precipitate was retained. The obtained precipitate was washed alternately with anhydrous ethanol and deionized water for 3 times. The precipitate was then transferred to a vacuum drying oven and dried at 5060° C. for 200 to 240 minutes. The dried product was ground to a particle size of 200 mesh to obtain a yellow powder of chitosan cinnamaldehyde Schiff base.
[0015] The present invention adopts the design of modified chitosan zinc oxide mainly for enhancing the antibacterial property and air permeability of the material, and realizes the synergistic effect between multi-component materials through the composite action of chitosan cinnamaldehyde Schiff base and silane-modified zinc oxide. Chitosan cinnamaldehyde Schiff base is prepared by Schiff base condensation reaction of chitosan and cinnamaldehyde in acetic acid and anhydrous ethanol medium, and the conjugated system of cinnamaldehyde is introduced into its molecular structure, which not only enhances the antibacterial property of chitosan, but also improves its chemical stability in the composite material; Silane-modified zinc oxide functionalizes the surface of nano-rod-shaped zinc oxide particles by isocyanate propyl triethoxysilane, giving it excellent dispersibility and interfacial compatibility, and further improves the air permeability and antibacterial activity of the material through the nano-rod-shaped structure. In the process of preparing modified chitosan zinc oxide, chitosan cinnamaldehyde Schiff base and silane-modified zinc oxide are fully compounded by ultrasonic dispersion and water bath stirring, wherein the spatial network structure of chitosan molecular chain and the surface activity of nano zinc oxide synergistically act, so that the composite material has uniform antibacterial component distribution and stable physical properties. In addition, during the composite preparation process, the formation process of flocculent precipitation was further optimized by adjusting the pH conditions and stirring rate to ensure the structural integrity and functionality of the composite product. In general, the present invention constructs a composite material system with significantly enhanced antibacterial and breathable properties through the biological activity provided by chitosan cinnamaldehyde Schiff base and the nano effect of silane-modified zinc oxide, which meets the dual needs of antibacterial and breathable properties in multi-scenario applications and provides new ideas and technical support for the development of functional materials.
[0016] Furthermore, the preparation method of the polyester fiber is as follows: polyethylene terephthalate chips, antioxidant 1010, and POE elastomer are added to a high-speed mixer, mixed at 300-500 rpm for 5-10 minutes at room temperature to obtain a uniformly dispersed raw material, then the uniformly dispersed filler is added to a twin-screw blending extruder, melt-blended at 250-280° C. for 30-45 minutes, and the melt blending rate is 300-500 rpm. During the blending process, modified chitosan zinc oxide and polyether modified silicone oil are gradually added thereto, and then a fiber masterbatch is obtained by extrusion, and then the fiber masterbatch is added to a melt spinning device, and spun at 260-280° C. to form polyester fibers.
[0017] Furthermore, the preparation method of the nanorod-shaped zinc oxide particles is as follows: by weight, 0.5-1.0 parts of zinc nitrate and 0.5-1.0 parts of urea are dissolved in 100-200 parts of deionized water, and stirred at a stirring rate of 300-500 rpm for 10-20 minutes to form a mixed solution; the mixed solution is transferred to a hydrothermal reactor, sealed and reacted at 90-95° C. for 240-360 minutes, and naturally cooled to room temperature after the reaction is completed, the reaction solution is filtered and the solid powder is retained, and the solid powder is washed with deionized water for 3-5 times, each washing time is 5-10 minutes, and the washed solid powder is placed in a vacuum drying oven at 50-60° C. and dried for 6-10 hours to obtain nanorod-shaped zinc oxide particles.
[0018] Furthermore, the average diameter of the nanorod-shaped zinc oxide particles is 50-100 nm, and the average length is 500-1000 nm.
[0019] The present invention adopts the design of nanorod-shaped zinc oxide particles mainly to enhance the flexibility and antibacterial properties of the material, and realizes the synergistic optimization of various performances through sophisticated preparation processes and unique nanostructures. First, the nanorod-shaped zinc oxide particles are prepared by zinc nitrate and urea under hydrothermal reaction conditions. Its one-dimensional nanorod-shaped morphology ensures a high specific surface area and good dispersibility, provides sufficient contact interface for the antibacterial activity of the material, and significantly enhances the physical coupling effect of the particles in the composite system. By strictly controlling the reaction conditions, including the ratio of zinc nitrate to urea, reaction temperature and time, the size uniformity and morphological integrity of the zinc oxide particles are ensured, and finally a nanorod-shaped structure with an average diameter of 50 to 100 nm and a length of 500 to 1000 nm is formed. This special geometric morphology not only gives the particles stronger antibacterial activity, but also enhances the flexibility of the material through its physical filling effect in the composite material. The high aspect ratio structure of nanorod-shaped zinc oxide can form a uniform distribution state in the composite material, and improve flexibility through physical intercalation with the matrix material. At the same time, the high surface activity brought by its specific surface area enables the particles to quickly contact with microorganisms, thereby achieving the purpose of high-efficiency antibacterial. The present invention optimizes the structure and preparation process of nanorod-shaped zinc oxide to achieve a synergistic improvement in flexibility and antibacterial properties, providing important technical support for the development of high-performance functional materials.
[0020] Furthermore, the preparation method of the antibacterial breathable yarn is as follows: polyester fiber, nylon fiber, cotton fiber and elastic fiber are spun by air-jet spinning, and the spinning tension is set to 8-15 cN, the twist is 300-500 twists / m, and the spinning speed is 100-200 m / min; the spun yarn is drafted, and the drafting ratio is controlled at 1.05-1.2, followed by twisting, and the twist coefficient is controlled at 3.5-4.5, and the yarn is wound into a tube, and the winding tension is controlled at 5-10 cN, thereby preparing the antibacterial breathable yarn.
[0021] Furthermore, the elastic fiber is Lycra fiber or spandex fiber.
[0022] The present invention adopts the design of antibacterial breathable yarn mainly to enhance the air permeability and antibacterial properties of textiles. Through the scientific combination of multiple fiber materials and precise process control, the synergistic optimization of yarn in functionality and mechanical properties is achieved. In the preparation process of the yarn, polyester fiber, nylon fiber, cotton fiber and elastic fiber are spun by air-spinning process, and the reasonable proportion of each component makes the yarn have both good mechanical properties and functional basis. The precise control of spinning tension, twist and spinning speed ensures the close combination between fibers and the uniformity of yarn structure, and then the strength and elasticity of the yarn are further improved by drafting and twisting process, wherein the adjustment of drafting ratio and twist coefficient optimizes the flexibility and tensile properties of the yarn, and the reasonable setting of winding tension ensures the stability of the yarn in subsequent processing. Polyester fiber is used as a reinforcing matrix of mechanical properties in the yarn, which is prepared by melt blending of polyethylene terephthalate slices with antioxidant 1010 and POE elastomer, giving the fiber excellent strength and flexibility. During the blending process, the modified chitosan zinc oxide and polyether modified silicone oil added gradually further enhance the antibacterial and breathable properties of the fiber. The modified chitosan zinc oxide is evenly dispersed in the fiber, providing a lasting antibacterial effect through its biological activity, while the polyether modified silicone oil improves the softness and moisture permeability of the fiber through its lubricity and hydrophilicity. In addition, the high wear resistance of nylon fiber in the yarn and the hygroscopic breathability of cotton fiber synergize with the elastic recovery of elastic fiber (such as Lycra fiber or spandex fiber) to further optimize the comprehensive performance of the yarn in antibacterial and breathable properties. Finally, through precise process design and the synergistic effect of each component, the antibacterial and breathable yarn prepared by the present invention can not only effectively inhibit the growth of microorganisms, but also maintain high breathability while taking into account high flexibility and durability, providing technical support for the development of high-performance textile materials.
[0023] The present invention also discloses an antibacterial breathable sock, wherein the antibacterial breathable sock is woven from the antibacterial breathable yarn;
[0024] The preparation method of the antibacterial breathable socks is as follows: using the antibacterial breathable yarn, knitting the socks through a knitting machine according to the sock weaving design requirements, the needle pitch of the knitting machine is 12 to 18 needles / inch, the weaving tension is 5 to 15 cN, and the weaving speed is 20 to 40 rpm; the knitting density is adjusted according to the functional requirements of different parts of the socks, wherein the knitting density of the sock bottom is appropriately reduced, the knitting density is controlled at 150 to 180 needles / square inch to enhance the air permeability, and the knitting density of the sock opening is appropriately increased. The knitting density is controlled at 200 to 240 needles per square inch to improve elasticity and fit; after knitting, the socks are sewed, the sewed process adopts a chain stitch method, and the sewing thread tension is controlled at 4 to 8 cN, and then the socks are shaped, the shaping temperature is 80 to 100° C., and the shaping time is 3 to 8 minutes; the shaped socks are heat-set, the heat-setting temperature is 120 to 150° C., and the setting time is 5 to 15 minutes; finally, antibacterial and breathable socks are prepared.
[0025] The present invention adopts the design of antibacterial breathable yarn mainly to enhance the antibacterial performance and comfort of antibacterial breathable socks, and realizes the overall improvement of socks in functionality and wearing experience by optimizing the combination of yarn and weaving process. In the present invention, the antibacterial breathable socks are woven from antibacterial breathable yarn, and the yarn has excellent antibacterial and breathable properties through reasonable component matching and precise process control, which lays a foundation for the performance of socks. In the knitting forming process of socks, the overall structure of socks is uniform and has good mechanical properties through the precise control of the needle pitch, weaving tension and weaving speed of the knitting machine. In order to meet the functional requirements of different parts, the socks bottom adopts a lower knitting density to enhance the air permeability, effectively remove the moisture of the foot, and improve the dry feeling of wearing; the socks opening part enhances the elasticity and fit by increasing the knitting density, ensuring that the socks are more comfortable and not easy to slip during wearing. After knitting forming, the chain stitching head seam process and the strictly controlled sewing thread tension are used to avoid the discomfort of the socks head seam, and at the same time improve the durability and overall aesthetics of the product. In addition, after the socks are formed, appropriate shaping and heat setting processes are used, among which the optimization of shaping temperature and time can further stabilize the size and shape of the socks, while the heat setting treatment improves the washing resistance and durability of the socks through structural solidification under high temperature conditions. The synergy between the various process links enables the socks to meet the antibacterial requirements while taking into account breathability, elasticity and durability, providing high quality guarantees for daily wear, exercise and special environments. The present invention achieves an organic combination of functionality and comfort through the precise design of yarn properties and weaving technology, providing technical support and market competitiveness for the development and promotion of antibacterial and breathable socks.
[0026] Beneficial technical effects
[0027] 1. The present invention is significantly superior to the prior art in terms of antibacterial properties and air permeability through the design of modified chitosan zinc oxide. The conjugated system of chitosan cinnamaldehyde Schiff base improves the antibacterial properties and chemical stability, and the surface functionalization of silane-modified zinc oxide enhances the dispersibility and air permeability of the material. The two achieve synergistic effects between components through uniform compounding, making the antibacterial components evenly distributed and having long-lasting performance. The present invention not only solves the technical pain point that it is difficult to balance antibacterial properties and air permeability in existing materials, but also ensures the structural integrity of the material by optimizing process conditions. It is suitable for medical, textile and other fields, and promotes the industry to develop in the direction of high performance and environmental protection, showing broad application prospects.
[0028] 2. The present invention adopts the design of nanorod-shaped zinc oxide particles, and through its high aspect ratio structure and excellent dispersibility, it achieves a synergistic improvement in flexibility and antibacterial performance, and has higher antibacterial efficiency and mechanical properties compared to the prior art. The special morphology and high surface area of the particles enhance the antibacterial activity, while improving the flexibility of the material through physical intercalation, solving the pain point that traditional materials are difficult to balance antibacterial and mechanical properties. Strict control of the preparation process ensures the uniformity of particle size and functional stability, which is suitable for medical, textile and other fields, providing innovative solutions for industry development and showing broad application prospects.
[0029] 3. The present invention innovatively achieves the coordinated optimization of air permeability, antibacterial properties and flexibility through the design of antibacterial breathable yarn, and significantly improves the comprehensive performance of the yarn compared with the prior art. Through the synergistic effect of the strength enhancement of polyester fiber, the wear resistance of nylon fiber, the moisture absorption and air permeability of cotton fiber and the recovery of elastic fiber, combined with the antibacterial activity of modified chitosan zinc oxide and the softness of polyether modified silicone oil, the yarn has the advantages of uniform structure and stable function, which solves the pain point of traditional textiles that it is difficult to balance antibacterial and comfort. It is suitable for medical, sports and home fields, and provides new technical support and application prospects for the textile industry to develop in the direction of high performance and multi-function.
[0030] 4. The present invention significantly improves the antibacterial property, breathability and wearing comfort of socks through the coordinated design of antibacterial breathable yarn and precise weaving process. Compared with the prior art, the present invention achieves functional optimization in the sock sole and sock opening area, which can not only efficiently remove moisture and keep dry, but also enhance elasticity and fit, solving the problem of traditional socks being easy to slip and not breathable. Through reasonable proportioning and process control, each component performs well in durability, dimensional stability and antibacterial persistence, and is suitable for daily use, sports and special environments. It provides a reliable solution for the upgrade of functional socks and promotes the industry to develop in the direction of high performance and comfort. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a SEM morphology image of the nanorod-shaped zinc oxide particles prepared in Example 1 of the present invention.
[0032] Figure 2 This is the infrared Fourier spectrum of the nanorod-shaped zinc oxide particles prepared in Example 1 of the present invention.
[0033] Figure 3 This is the infrared Fourier spectrum of the silane-modified zinc oxide prepared in Example 1 of the present invention.
[0034] Figure 4 This is the infrared Fourier spectrum of the chitosan cinnamaldehyde Schiff base prepared in Example 1 of the present invention.
[0035] Figure 5 This is the infrared Fourier spectrum of the modified chitosan zinc oxide prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0037] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0038] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies
[0039]
[0040]
[0041] Embodiment 1
[0042] An antibacterial breathable yarn, the antibacterial breathable yarn of this embodiment is obtained by spinning polyester fiber, nylon fiber, cotton fiber and elastic fiber;
[0043] The mass ratio of polyester fiber, nylon fiber, cotton fiber and elastic fiber in this embodiment is 40:20:10:5;
[0044] The polyester fiber of this embodiment is prepared from the following components in parts by weight: 85 parts of polyethylene terephthalate chips, 3.0 parts of modified chitosan zinc oxide, 0.3 parts of antioxidant 1010, 1.0 parts of POE elastomer, 2.0 parts of polyether modified silicone oil, and 1.0 parts of polyethylene glycol 200;
[0045] The modified chitosan zinc oxide of this embodiment is prepared by combining chitosan cinnamaldehyde Schiff base and silane-modified zinc oxide; the chitosan cinnamaldehyde Schiff base is obtained by the Schiff base condensation reaction of chitosan and cinnamaldehyde in acetic acid and anhydrous ethanol medium; the silane-modified zinc oxide is isocyanate propyl triethoxysilane-modified nanorod-shaped zinc oxide particles;
[0046] The preparation method of the modified chitosan zinc oxide of the present embodiment is as follows: by weight, 10.0 parts of chitosan cinnamaldehyde Schiff base are added to 500 parts of deionized water, and then the pH of the mixed solution is adjusted to 3.0 with a 3.0wt.% acetic acid solution, and after the adjustment, the solution is stirred at a stirring rate of 200rpm at 60°C for 20min, and then 40.0 parts of silane-modified zinc oxide are added to the solution, and the mixed solution is placed in an ultrasonic device for ultrasonication for 20min, and then stirred in a 50°C water bath for 30min, and after the stirring is completed, the pH of the mixed solution is adjusted to 8.8 with a 5wt.% sodium hydroxide solution, and after the adjustment is completed, a flocculent precipitate is formed in the mixed solution, and then the mixed solution is filtered and the precipitate is retained, and the precipitate is washed 3 times with deionized water, and after the washing is completed, it is dried in a vacuum drying oven at 50°C for 8h, and the dried product is ground to a particle size of 200 meshes to obtain modified chitosan zinc oxide.
[0047] The preparation method of the silane-modified zinc oxide of the present embodiment is as follows: by weight, 15.0 parts of ethyl glycolate and 40.0 parts of isocyanatepropyltriethoxysilane are added to a beaker, and 0.20 parts of dibutyltin dilaurate are added, and the mixture is stirred at 40.0°C at a stirring rate of 300 rpm for 200 min to form a uniform mixed solution, and then 100 parts of nanorod-shaped zinc oxide particles, 200 parts of anhydrous ethanol and 150 parts of deionized water are added to the mixed solution in sequence, and then the mixed solution is ultrasonicated for 30 min, and after the ultrasonic treatment, the pH of the solution is adjusted to 9.8 with a 5wt.% sodium hydroxide solution, and after the pH is adjusted, the mixed solution is stirred in a water area at 60°C at a stirring rate of 300 rpm for 240 min, and after the stirring is completed, the mixed solution is filtered and the precipitate is retained, and then the precipitate is washed alternately with deionized water and anhydrous ethanol for 3 times, and the washed precipitate is dried at 50°C for 6 h to obtain the silane-modified zinc oxide.
[0048] The preparation method of the chitosan cinnamaldehyde Schiff base of the present embodiment is as follows: by weight, 10.0 parts of chitosan are dissolved in 100 parts of 1wt.% acetic acid solution to obtain a chitosan solution, and 7.0 parts of cinnamaldehyde are dissolved in 300 parts of anhydrous ethanol to obtain a cinnamaldehyde solution, and then the cinnamaldehyde solution is added dropwise to the chitosan solution. After the dropwise addition is completed, the mixed solution is placed in an oil bath at 40°C, and stirred at a stirring rate of 350rpm for 300min. After the stirring is completed, a 5wt.% sodium hydroxide solution is slowly added dropwise to the solution, and the pH of the solution is adjusted to 10 until a flocculent precipitate is formed in the solution. Then, the mixed solution is filtered and the precipitate is retained. The obtained precipitate is washed alternately with anhydrous ethanol and deionized water for 3 times, and then the precipitate is transferred to a vacuum drying oven and dried at 50°C for 200min. The dried product is ground to a particle size of 200 meshes to obtain a yellow powder of chitosan cinnamaldehyde Schiff base.
[0049] The preparation method of the polyester fiber of this embodiment is as follows: polyethylene terephthalate chips, antioxidant 1010, and POE elastomer are added to a high-speed mixer, mixed at 300 rpm for 5 minutes at room temperature to obtain a uniformly dispersed raw material, then the uniformly dispersed filler is added to a twin-screw blending extruder, melt-blended at 250° C. for 30 minutes, and the melt-blending rate is 300 rpm. During the blending process, modified chitosan zinc oxide and polyether-modified silicone oil are gradually added thereto, and then a fiber masterbatch is obtained by extrusion, and then the fiber masterbatch is added to a melt spinning device, and spun at 260° C. to form polyester fibers.
[0050] The preparation method of the nanorod-shaped zinc oxide particles of the present embodiment is as follows: by weight, 0.5 parts of zinc nitrate and 0.5 parts of urea are dissolved in 100 parts of deionized water, and stirred at a stirring rate of 300 rpm for 10 minutes to form a mixed solution; the mixed solution is transferred to a hydrothermal reactor, and the mixture is sealed and reacted at 90° C. for 240 minutes. After the reaction is completed, the mixture is naturally cooled to room temperature, the reaction solution is filtered and the solid powder is retained, and the solid powder is washed with deionized water for 3 times, each washing time is 5 minutes, and the washed solid powder is placed in a vacuum drying oven at 50° C. and dried for 6 hours to obtain nanorod-shaped zinc oxide particles.
[0051] The average diameter of the nanorod-shaped zinc oxide particles in this embodiment is 50 nm, and the average length is 500 nm.
[0052] The preparation method of the antibacterial breathable yarn of the present embodiment is as follows: polyester fiber, nylon fiber, cotton fiber and elastic fiber are spun by air-jet spinning, and the spinning tension is set to 8 cN, the twist is 300 twists / m, and the spinning speed is 100 m / min; the spun yarn is stretched, and the stretching ratio of the present embodiment is controlled at 1.05, followed by twisting, and the twist coefficient of the present embodiment is controlled at 3.5, and the yarn is wound into a tube, and the winding tension of the present embodiment is controlled at 5 cN, thereby preparing the antibacterial breathable yarn.
[0053] The elastic fiber in this embodiment is Lycra fiber.
[0054] The present invention also discloses an antibacterial breathable sock, and the antibacterial breathable sock of this embodiment is woven from the antibacterial breathable yarn of this embodiment;
[0055] The preparation method of the antibacterial breathable socks of the present embodiment is as follows: the antibacterial breathable yarn of the present embodiment is used, and the socks are knitted into shape by a knitting machine according to the sock weaving design requirements. The needle pitch of the knitting machine of the present embodiment is 12 needles / inch, the weaving tension is 5cN, and the weaving speed is 20rpm; the knitting density is adjusted according to the functional requirements of different parts of the socks, wherein the knitting density of the sock bottom is appropriately reduced, and the knitting density is controlled at 150 needles / square inch to enhance the air permeability, and the knitting density of the sock opening is appropriately increased, and the knitting density is controlled at 200 needles / square inch to enhance the elasticity and fit; after knitting, the socks are sewed, and the sewed head process of the present embodiment adopts a chain stitch method, and the sewing thread tension is controlled at 4cN, and then the socks are shaped, and the shaping temperature of the present embodiment is 80°C, and the shaping time is 3min; the shaped socks are heat-set, and the heat-setting temperature of the present embodiment is 120°C, and the setting time is 5min; and finally, the antibacterial breathable socks are prepared.
[0056] Combination Figures 1 to 5 The characterization results show that the present invention successfully prepared nanorod-shaped zinc oxide particles through Example 1, and the infrared Fourier spectrum ( Figure 2 ) verified its surface characteristics, among which the -1 The broadband absorption peak at 869 cm is attributed to the OH stretching vibration of the hydroxyl groups on the ZnO surface or adsorbed water molecules, while the -1 The characteristic peak at is caused by the bending vibration of Zn-O-Zn. Figure 3 ), successfully achieved the surface grafting of nanorod-shaped zinc oxide, and the changes of characteristic peaks were observed in the infrared spectrum, including 3369cm -1 The stretching vibration peaks of NH and Si-X at 2926 cm -1 and 2856cm -1 – CH2 doublet, and 1716cm-1 and 869cm -1 The peaks at the positions correspond to the characteristic peaks of amide group and Zn-O and Si-O superposition, respectively, proving that IPTS has been successfully grafted onto the surface of zinc oxide. Figure 4 It can be confirmed that the present invention successfully prepared chitosan cinnamaldehyde Schiff base, and the infrared spectrum at 1632cm -1 The C=N stretching vibration absorption peak at 10 indicates that –NH2 in chitosan and –CHO in cinnamaldehyde form a Schiff base structure through condensation reaction. Figure 5 It further shows that the composite modification of chitosan cinnamaldehyde Schiff base and zinc oxide has been successfully achieved, 749cm -1 and 688cm -1 The vibration peaks of benzene ring CH and olefin clearly characterize the formation of the modified structure. In summary, the present invention successfully constructs a modified chitosan composite material based on nanorod-shaped zinc oxide through multi-step functional modification, and the chemical modification at each stage has been fully verified.
[0057] Embodiment 2
[0058] An antibacterial breathable yarn, the antibacterial breathable yarn of this embodiment is obtained by spinning polyester fiber, nylon fiber, cotton fiber and elastic fiber;
[0059] The mass ratio of polyester fiber, nylon fiber, cotton fiber and elastic fiber in this embodiment is 46:23:13:7;
[0060] The polyester fiber of this embodiment is prepared from the following components in parts by weight: 87 parts of polyethylene terephthalate chips, 3.6 parts of modified chitosan zinc oxide, 0.4 parts of antioxidant 1010, 1.3 parts of POE elastomer, 2.3 parts of polyether modified silicone oil, and 1.3 parts of polyethylene glycol 200;
[0061] The modified chitosan zinc oxide of this embodiment is prepared by combining chitosan cinnamaldehyde Schiff base and silane-modified zinc oxide; the chitosan cinnamaldehyde Schiff base is obtained by the Schiff base condensation reaction of chitosan and cinnamaldehyde in acetic acid and anhydrous ethanol medium; the silane-modified zinc oxide is isocyanate propyl triethoxysilane-modified nanorod-shaped zinc oxide particles;
[0062] The preparation method of the modified chitosan zinc oxide of the present embodiment is as follows: by weight, 11.5 parts of chitosan cinnamaldehyde Schiff base are added to 530 parts of deionized water, and then the pH of the mixed solution is adjusted to 3.3 with a 3.0wt.% acetic acid solution, and after the adjustment, the solution is stirred at a stirring rate of 215rpm at 63°C for 23min, and then 43.0 parts of silane-modified zinc oxide are added to the solution, and the mixed solution is placed in an ultrasonic device for ultrasonication for 23min, and then stirred in a 53°C water bath for 35min, and after the stirring is completed, the pH of the mixed solution is adjusted to 9.0 with a 5wt.% sodium hydroxide solution, and after the adjustment, a flocculent precipitate is formed in the mixed solution, and then the mixed solution is filtered and the precipitate is retained, and the precipitate is washed with deionized water for 3 times, and after the washing is completed, it is dried in a vacuum drying oven at 53°C for 9h, and the dried product is ground to a particle size of 200 mesh to obtain a modified chitosan zinc oxide.
[0063] The preparation method of the silane-modified zinc oxide of the present embodiment is as follows: by weight, 16.5 parts of ethyl glycolate and 43.0 parts of isocyanatepropyltriethoxysilane are added to a beaker, and 0.26 parts of dibutyltin dilaurate are added, and stirred at 41.5° C. and 315 rpm for 212 min to form a uniform mixed solution, and then 115 parts of nanorod-shaped zinc oxide particles, 215 parts of anhydrous ethanol and 153 parts of deionized water are added to the mixed solution in sequence, and then the mixed solution is ultrasonicated for 35 min, and after the ultrasonic treatment, the pH of the solution is adjusted to 9.9 with a 5wt.% sodium hydroxide solution, and after the pH is adjusted, the mixed solution is stirred in a water area of 61.5° C. and 330 rpm for 258 min, and after the stirring is completed, the mixed solution is filtered and the precipitate is retained, and then it is washed alternately with deionized water and anhydrous ethanol for 4 times, and the washed precipitate is dried at 53° C. for 7 h to obtain the silane-modified zinc oxide.
[0064] The preparation method of the chitosan cinnamaldehyde Schiff base of the present embodiment is as follows: by weight, 11.5 parts of chitosan are dissolved in 106 parts of 1wt.% acetic acid solution to obtain a chitosan solution, and 7.9 parts of cinnamaldehyde are dissolved in 330 parts of anhydrous ethanol to obtain a cinnamaldehyde solution, and then the cinnamaldehyde solution is added dropwise to the chitosan solution. After the dropwise addition is completed, the mixed solution is placed in an oil bath at 43°C, and stirred at a stirring rate of 365rpm for 318min. After the stirring is completed, a 5wt.% sodium hydroxide solution is slowly added dropwise to the solution, and the pH of the solution is adjusted to 10 until a flocculent precipitate is formed in the solution. Then, the mixed solution is filtered and the precipitate is retained. The obtained precipitate is washed alternately with anhydrous ethanol and deionized water for 3 times, and then the precipitate is transferred to a vacuum drying oven and dried at 53°C for 212min. The dried product is ground to a particle size of 200 meshes to obtain a yellow powder of chitosan cinnamaldehyde Schiff base.
[0065] The preparation method of the polyester fiber of this embodiment is as follows: polyethylene terephthalate chips, antioxidant 1010, and POE elastomer are added to a high-speed mixer, mixed at 360 rpm for 7 minutes at room temperature to obtain a uniformly dispersed raw material, then the uniformly dispersed filler is added to a twin-screw blending extruder, melt-blended at 259° C. for 35 minutes, and the melt-blending rate is 360 rpm. During the blending process, modified chitosan zinc oxide and polyether-modified silicone oil are gradually added thereto, and then a fiber masterbatch is obtained by extrusion, and then the fiber masterbatch is added to a melt spinning device, and spun at 266° C. to form polyester fibers.
[0066] The preparation method of the nanorod-shaped zinc oxide particles of this embodiment is as follows: by weight, 0.65 parts of zinc nitrate and 0.65 parts of urea are dissolved in 130 parts of deionized water, and stirred at a stirring rate of 360 rpm for 13 minutes to form a mixed solution; the mixed solution is transferred to a hydrothermal reactor, sealed and reacted at 92° C. for 276 minutes, and naturally cooled to room temperature after the reaction is completed, the reaction solution is filtered and the solid powder is retained, and the solid powder is washed with deionized water for 4 times, each washing time is 6.5 minutes, and the washed solid powder is placed in a vacuum drying oven at 53° C. and dried for 7 hours to obtain nanorod-shaped zinc oxide particles.
[0067] The average diameter of the nanorod-shaped zinc oxide particles in this embodiment is 65 nm, and the average length is 650 nm.
[0068] The preparation method of the antibacterial breathable yarn of the present embodiment is as follows: polyester fiber, nylon fiber, cotton fiber and elastic fiber are spun by air-jet spinning, and the spinning tension is set to 10 cN, the twist is 360 twists / m, and the spinning speed is 130 m / min; the spun yarn is stretched, and the stretching ratio of the present embodiment is controlled at 1.1, and then twisted, and the twist coefficient of the present embodiment is controlled at 3.8, and the yarn is wound into a tube, and the winding tension of the present embodiment is controlled at 6.5 cN, thereby preparing the antibacterial breathable yarn.
[0069] The elastic fiber of this embodiment is spandex fiber.
[0070] The present invention also discloses an antibacterial breathable sock, and the antibacterial breathable sock of this embodiment is woven from the antibacterial breathable yarn of this embodiment;
[0071] The preparation method of the antibacterial breathable socks of the present embodiment is as follows: the antibacterial breathable yarn of the present embodiment is used, and the socks are knitted into shape by a knitting machine according to the sock weaving design requirements. The needle pitch of the knitting machine of the present embodiment is 14 needles / inch, the weaving tension is 8cN, and the weaving speed is 26rpm; the knitting density is adjusted according to the functional requirements of different parts of the socks, wherein the knitting density of the sock bottom is appropriately reduced, and the knitting density is controlled at 159 needles / square inch to enhance the air permeability, and the knitting density of the sock opening is appropriately increased, and the knitting density is controlled at 212 needles / square inch to enhance the elasticity and fit; after knitting, the socks are sewed, and the sewed head process of the present embodiment adopts a chain stitch method, and the sewing thread tension is controlled at 5.2cN, and then the socks are shaped, and the shaping temperature of the present embodiment is 86°C, and the shaping time is 4.5min; the shaped socks are heat-set, and the heat-setting temperature of the present embodiment is 129°C, and the setting time is 8min; and finally, the antibacterial breathable socks are prepared.
[0072] Embodiment 3
[0073] An antibacterial breathable yarn, the antibacterial breathable yarn of this embodiment is obtained by spinning polyester fiber, nylon fiber, cotton fiber and elastic fiber;
[0074] The mass ratio of polyester fiber, nylon fiber, cotton fiber and elastic fiber in this embodiment is 53:26:14:7;
[0075] The polyester fiber of this embodiment is prepared from the following components in parts by weight: 88 parts of polyethylene terephthalate chips, 4.2 parts of modified chitosan zinc oxide, 0.4 parts of antioxidant 1010, 1.6 parts of POE elastomer, 2.6 parts of polyether modified silicone oil, and 1.6 parts of polyethylene glycol 200;
[0076] The modified chitosan zinc oxide of this embodiment is prepared by combining chitosan cinnamaldehyde Schiff base and silane-modified zinc oxide; the chitosan cinnamaldehyde Schiff base is obtained by the Schiff base condensation reaction of chitosan and cinnamaldehyde in acetic acid and anhydrous ethanol medium; the silane-modified zinc oxide is isocyanate propyl triethoxysilane-modified nanorod-shaped zinc oxide particles;
[0077] The preparation method of the modified chitosan zinc oxide of the present embodiment is as follows: by weight, 13 parts of chitosan cinnamaldehyde Schiff base are added to 560 parts of deionized water, and then the pH of the mixed solution is adjusted to 3.6 with a 3.0wt.% acetic acid solution, and after the adjustment, the solution is stirred at a stirring rate of 230rpm at 66°C for 26min, and then 46 parts of silane-modified zinc oxide are added to the solution, and the mixed solution is placed in an ultrasonic device for ultrasonication for 26min, and then stirred in a 56°C water bath for 39min, and after the stirring is completed, the pH of the mixed solution is adjusted to 9.0 with a 5wt.% sodium hydroxide solution, and after the adjustment, a flocculent precipitate is formed in the mixed solution, and then the mixed solution is filtered and the precipitate is retained, and the precipitate is washed with deionized water for 3 times, and after the washing is completed, it is dried in a vacuum drying oven at 56°C for 10h, and the dried product is ground to a particle size of 200 mesh to obtain a modified chitosan zinc oxide.
[0078] The preparation method of the silane-modified zinc oxide in this embodiment is as follows: by weight, 18 parts of ethyl glycolate and 46 parts of isocyanatepropyltriethoxysilane are added to a beaker, and 0.32 parts of dibutyltin dilaurate are added, and stirred at 43°C at a stirring rate of 330 rpm for 224 min to form a uniform mixed solution, and then 130 parts of nanorod-shaped zinc oxide particles, 230 parts of anhydrous ethanol and 156 parts of deionized water are added to the mixed solution in sequence, and then the mixed solution is ultrasonicated for 39 min, and after the ultrasonic treatment, the pH of the solution is adjusted to 10.1 with a 5wt.% sodium hydroxide solution, and after the pH is adjusted, the mixed solution is stirred in a water area at 63°C at a stirring rate of 360 rpm for 276 min, and after the stirring is completed, the mixed solution is filtered and the precipitate is retained, and then the precipitate is washed alternately with deionized water and anhydrous ethanol for 4 times, and the washed precipitate is dried at 56°C for 8 h to obtain the silane-modified zinc oxide.
[0079] The preparation method of the chitosan cinnamaldehyde Schiff base of the present embodiment is as follows: by weight, 13 parts of chitosan are dissolved in 112 parts of 1wt.% acetic acid solution to obtain a chitosan solution, and 8.6 parts of cinnamaldehyde are dissolved in 360 parts of anhydrous ethanol to obtain a cinnamaldehyde solution, and then the cinnamaldehyde solution is added dropwise to the chitosan solution. After the dropwise addition is completed, the mixed solution is placed in an oil bath at 46°C, and stirred at a stirring rate of 380rpm for 336min. After the stirring is completed, a 5wt.% sodium hydroxide solution is slowly added dropwise to the solution, and the pH of the solution is adjusted to 10 until a flocculent precipitate is formed in the solution. Then, the mixed solution is filtered and the precipitate is retained. The obtained precipitate is washed alternately with anhydrous ethanol and deionized water for 3 times, and then the precipitate is transferred to a vacuum drying oven and dried at 56°C for 224min. The dried product is ground to a particle size of 200 meshes to obtain a yellow powder of chitosan cinnamaldehyde Schiff base.
[0080] The preparation method of the polyester fiber of this embodiment is as follows: polyethylene terephthalate chips, antioxidant 1010, and POE elastomer are added to a high-speed mixer, mixed at 420 rpm for 8 minutes at room temperature to obtain a uniformly dispersed raw material, then the uniformly dispersed filler is added to a twin-screw blending extruder, melt-blended at 268° C. for 39 minutes, and the melt-blending rate is 420 rpm. During the blending process, modified chitosan zinc oxide and polyether-modified silicone oil are gradually added thereto, and then a fiber masterbatch is obtained by extrusion, and then the fiber masterbatch is added to a melt spinning device, and spun at 272° C. to form polyester fibers.
[0081] The preparation method of the nanorod-shaped zinc oxide particles of the present embodiment is as follows: by weight, 0.8 parts of zinc nitrate and 0.8 parts of urea are dissolved in 160 parts of deionized water, and stirred at a stirring rate of 420 rpm for 16 minutes to form a mixed solution; the mixed solution is transferred to a hydrothermal reactor, sealed and reacted at 93° C. for 316 minutes, and naturally cooled to room temperature after the reaction is completed, the reaction solution is filtered and the solid powder is retained, and the solid powder is washed with deionized water for 4 times, each washing time is 8 minutes, and the washed solid powder is placed in a vacuum drying oven at 56° C. and dried for 8 hours to obtain nanorod-shaped zinc oxide particles.
[0082] The average diameter of the nanorod-shaped zinc oxide particles in this embodiment is 80 nm, and the average length is 800 nm.
[0083] The preparation method of the antibacterial breathable yarn of the present embodiment is as follows: polyester fiber, nylon fiber, cotton fiber and elastic fiber are spun by air-jet spinning, and the spinning tension is set to 12 cN, the twist is 420 twists / m, and the spinning speed is 160 m / min; the spun yarn is stretched, and the stretching ratio of the present embodiment is controlled at 1.15, and then twisted, and the twist coefficient of the present embodiment is controlled at 4.1, and the yarn is wound into a tube, and the winding tension of the present embodiment is controlled at 8 cN, thereby preparing the antibacterial breathable yarn.
[0084] The elastic fiber in this embodiment is Lycra fiber.
[0085] The present invention also discloses an antibacterial breathable sock, and the antibacterial breathable sock of this embodiment is woven from the antibacterial breathable yarn of this embodiment;
[0086] The preparation method of the antibacterial breathable socks of the present embodiment is as follows: the antibacterial breathable yarn of the present embodiment is used, and the socks are knitted into shape by a knitting machine according to the sock weaving design requirements. The needle pitch of the knitting machine of the present embodiment is 16 needles / inch, the weaving tension is 11cN, and the weaving speed is 32rpm; the knitting density is adjusted according to the functional requirements of different parts of the socks, wherein the knitting density of the sock bottom is appropriately reduced, and the knitting density is controlled at 168 needles / square inch to enhance the air permeability, and the knitting density of the sock opening is appropriately increased, and the knitting density is controlled at 224 needles / square inch to enhance the elasticity and fit; after knitting, the socks are sewed, and the sewed head process of the present embodiment adopts a chain stitch method, and the sewing thread tension is controlled at 6.4cN, and then the socks are shaped, and the shaping temperature of the present embodiment is 92°C, and the shaping time is 6min; the shaped socks are heat-set, and the heat-setting temperature of the present embodiment is 138°C, and the setting time is 11min; and finally, the antibacterial breathable socks are prepared.
[0087] Embodiment 4
[0088] An antibacterial breathable yarn, the antibacterial breathable yarn of this embodiment is obtained by spinning polyester fiber, nylon fiber, cotton fiber and elastic fiber;
[0089] The mass ratio of polyester fiber, nylon fiber, cotton fiber and elastic fiber in this embodiment is 60:30:20:10;
[0090] The polyester fiber of this embodiment is prepared from the following components in parts by weight: 90 parts of polyethylene terephthalate chips, 5.0 parts of modified chitosan zinc oxide, 0.5 parts of antioxidant 1010, 2.0 parts of POE elastomer, 3.0 parts of polyether modified silicone oil, and 2.0 parts of polyethylene glycol 200;
[0091] The modified chitosan zinc oxide of this embodiment is prepared by combining chitosan cinnamaldehyde Schiff base and silane-modified zinc oxide; the chitosan cinnamaldehyde Schiff base is obtained by the Schiff base condensation reaction of chitosan and cinnamaldehyde in acetic acid and anhydrous ethanol medium; the silane-modified zinc oxide is isocyanate propyl triethoxysilane-modified nanorod-shaped zinc oxide particles;
[0092] The preparation method of the modified chitosan zinc oxide of the present embodiment is as follows: by weight, 15.0 parts of chitosan cinnamaldehyde Schiff base are added to 600 parts of deionized water, and then the pH of the mixed solution is adjusted to 4.0 with a 3.0wt.% acetic acid solution, and after the adjustment, the solution is stirred at a stirring rate of 250rpm at 70°C for 30min, and then 50.0 parts of silane-modified zinc oxide are added to the solution, and the mixed solution is placed in an ultrasonic device for ultrasonication for 30min, and then stirred in a 60°C water bath for 45min, and after the stirring is completed, the pH of the mixed solution is adjusted to 9.2 with a 5wt.% sodium hydroxide solution, and after the adjustment, a flocculent precipitate is formed in the mixed solution, and then the mixed solution is filtered and the precipitate is retained, and the precipitate is washed 3 times with deionized water, and after the washing is completed, it is dried in a vacuum drying oven at 60°C for 12h, and the dried product is ground to a particle size of 200 meshes to obtain modified chitosan zinc oxide.
[0093] The preparation method of the silane-modified zinc oxide of the present embodiment is as follows: by weight, 20.0 parts of ethyl glycolate and 50.0 parts of isocyanatepropyltriethoxysilane are added to a beaker, and 0.40 parts of dibutyltin dilaurate are added, and the mixture is stirred at 45.0°C and 350 rpm for 240 min to form a uniform mixed solution, and then 150 parts of nanorod-shaped zinc oxide particles, 250 parts of anhydrous ethanol and 160 parts of deionized water are added to the mixed solution in sequence, and then the mixed solution is ultrasonicated for 45 min, and after the ultrasonic treatment, the pH of the solution is adjusted to 10.2 with a 5wt.% sodium hydroxide solution, and after the pH is adjusted, the mixed solution is stirred in a water area at 65°C at a stirring rate of 400 rpm for 300 min, and after the stirring is completed, the mixed solution is filtered and the precipitate is retained, and then the precipitate is washed alternately with deionized water and anhydrous ethanol for 5 times, and the washed precipitate is dried at 60°C for 10 h to obtain the silane-modified zinc oxide.
[0094] The preparation method of the chitosan cinnamaldehyde Schiff base of the present embodiment is as follows: by weight, 15.0 parts of chitosan are dissolved in 120 parts of 1wt.% acetic acid solution to obtain a chitosan solution, and 10.0 parts of cinnamaldehyde are dissolved in 400 parts of anhydrous ethanol to obtain a cinnamaldehyde solution, and then the cinnamaldehyde solution is added dropwise to the chitosan solution. After the dropwise addition is completed, the mixed solution is placed in an oil bath at 50°C, and stirred at a stirring rate of 400rpm for 360min. After the stirring is completed, a 5wt.% sodium hydroxide solution is slowly added dropwise to the solution, and the pH of the solution is adjusted to 10 until a flocculent precipitate is formed in the solution. Then, the mixed solution is filtered and the precipitate is retained. The obtained precipitate is washed alternately with anhydrous ethanol and deionized water for 3 times, and then the precipitate is transferred to a vacuum drying oven and dried at 60°C for 240min. The dried product is ground to a particle size of 200 meshes to obtain a yellow powder of chitosan cinnamaldehyde Schiff base.
[0095] The preparation method of the polyester fiber of this embodiment is as follows: polyethylene terephthalate chips, antioxidant 1010, and POE elastomer are added to a high-speed mixer, mixed at 500 rpm for 10 minutes at room temperature to obtain a uniformly dispersed raw material, then the uniformly dispersed filler is added to a twin-screw blending extruder, melt-blended at 280°C for 45 minutes, and the melt-blending rate is 500 rpm. During the blending process, modified chitosan zinc oxide and polyether modified silicone oil are gradually added thereto, and then a fiber masterbatch is obtained by extrusion, and then the fiber masterbatch is added to a melt spinning device, and spun at 280°C to form polyester fibers.
[0096] The preparation method of the nanorod-shaped zinc oxide particles of the present embodiment is as follows: by weight, 1.0 part of zinc nitrate and 1.0 part of urea are dissolved in 200 parts of deionized water, and stirred at a stirring rate of 500 rpm for 20 minutes to form a mixed solution; the mixed solution is transferred to a hydrothermal reactor, sealed and reacted at 95° C. for 360 minutes, and naturally cooled to room temperature after the reaction is completed, the reaction solution is filtered and the solid powder is retained, and the solid powder is washed with deionized water for 5 times, each washing time is 10 minutes, and the washed solid powder is placed in a vacuum drying oven at 60° C. and dried for 10 hours to obtain nanorod-shaped zinc oxide particles.
[0097] The average diameter of the nanorod-shaped zinc oxide particles in this embodiment is 100 nm, and the average length is 1000 nm.
[0098] The preparation method of the antibacterial breathable yarn of the present embodiment is as follows: polyester fiber, nylon fiber, cotton fiber and elastic fiber are spun by air-jet spinning, and the spinning tension is set to 15 cN, the twist is 500 twists / m, and the spinning speed is 200 m / min; the spun yarn is stretched, and the stretching ratio is controlled at 1.2 in the present embodiment, and then twisted, and the twist coefficient is controlled at 4.5 in the present embodiment, and the yarn is wound into a tube, and the winding tension is controlled at 10 cN in the present embodiment, thereby preparing the antibacterial breathable yarn.
[0099] The elastic fiber of this embodiment is spandex fiber.
[0100] The present invention also discloses an antibacterial breathable sock, and the antibacterial breathable sock of this embodiment is woven from the antibacterial breathable yarn of this embodiment;
[0101] The preparation method of the antibacterial breathable socks of the present embodiment is as follows: the antibacterial breathable yarn of the present embodiment is used, and the socks are knitted into shape by a knitting machine according to the sock weaving design requirements. The needle pitch of the knitting machine of the present embodiment is 18 needles / inch, the weaving tension is 15cN, and the weaving speed is 40rpm; the knitting density is adjusted according to the functional requirements of different parts of the socks, wherein the knitting density of the sock bottom is appropriately reduced, and the knitting density is controlled at 180 needles / square inch to enhance the air permeability, and the knitting density of the sock opening is appropriately increased, and the knitting density is controlled at 240 needles / square inch to enhance the elasticity and fit; after knitting, the socks are sewed, and the sewed head process of the present embodiment adopts a chain stitch method, and the sewing thread tension is controlled at 8cN, and then the socks are shaped, and the shaping temperature of the present embodiment is 100°C, and the shaping time is 8min; the shaped socks are heat-set, and the heat-setting temperature of the present embodiment is 150°C, and the setting time is 15min; and finally, the antibacterial breathable socks are prepared.
[0102] Comparative Example 1
[0103] The method is basically the same as Example 1, except that the modified chitosan zinc oxide is replaced by an equal amount of rod-shaped nano zinc oxide particles, so the rod-shaped nano zinc oxide is not modified by chitosan cinnamaldehyde Schiff base and silane.
[0104] Comparative Example 2
[0105] The method is basically the same as Example 1, except that an equal amount of rod-shaped nano zinc oxide particles are used without being modified by silane.
[0106] Comparative Example 3
[0107] The method is basically the same as Example 1, except that commercial nano zinc oxide particles are used instead of rod-shaped nano zinc oxide particles. The commercial nano zinc oxide particles are usually spherical particles purchased from Shijiazhuang Jixin Zinc Industry Co., Ltd.
[0108] Comparative Example 4
[0109] The method is basically the same as Example 1, except that no POE elastomer is added when preparing the polyester fiber, and the other components remain unchanged.
[0110] Comparative Example 5
[0111] The method is basically the same as Example 1, except that no polyether-modified silicone oil is added in the preparation of the polyester fiber, and the proportions of other components remain unchanged.
[0112] Comparative Example 6
[0113] The method is basically the same as Example 1, except that no POE elastomer is added when preparing the polyester fiber, and the other components remain unchanged.
[0114] Performance Test:
[0115] Mechanical properties: The mechanical properties of yarns were tested using a YG061 electronic single yarn strength tester (Laizhou Electronic Instrument Co., Ltd.) in accordance with GB / T3916-2013 "Determination of the breaking strength and elongation of single yarns in textile package yarns". The test parameters were set as follows: test gauge 500 mm, tensile speed 500 mm / min, pre-tension 0.5±0.1 cN / tex. Each group of blended yarns was tested 60 times, and the breaking strength data were recorded and averaged. Combined with the measured yarn linear density, the breaking strength and elongation at break were calculated.
[0116] Air permeability: According to the fabric air permeability test standard, the air permeability of the sock sample is measured. Before the test, the sample is placed in a standard environment and adjusted to equilibrium. The air permeability is characterized by measuring the air flow rate through a unit area of fabric per unit time under a specified pressure difference using a fabric air permeability tester. During the test, the sample is fixed flat on the test head of the tester, a standard pressure difference is applied, and the air flow rate is recorded. The test results are expressed in milliliters per square centimeter second (mL / cm 2 ·s). Each sample is tested repeatedly at different locations, and the average value is taken as the final air permeability. The larger the air permeability value, the better the air permeability of the fabric and the more comfortable it is to wear.
[0117] Antibacterial property: The antibacterial property of yarn was tested according to GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method". The experimental steps were carried out in accordance with standard 4.3.2.2, including the preparation of culture medium, culture of bacterial solution and dilution operation. The details strictly followed the standard requirements. The sample was placed in an air bath constant temperature shaker at 24℃±1℃ and a speed of 150r / min for 18 hours, and 1mL of solution was taken and diluted 10 2 , 10 3 , 104 times, and then plate culture was carried out and cultured at 37℃±1℃ for 24h. The concentration of the bacterial solution was adjusted to 1×109~5×109CFU / mL by turbidimetry, and the concentration of live bacteria in the sample conical flask was finally calculated according to the formula. The results were quantitatively expressed as the antibacterial rate to express the antibacterial effect of the yarn.
[0118] The properties of the yarns and antibacterial breathable socks of Examples 1 to 4 and Comparative Examples 1 to 6 are summarized in Table 2.
[0119] Table 2 Performance summary of yarns and antibacterial breathable socks of Examples 1 to 4 and Comparative Examples 1 to 6
[0120]
[0121] The main difference between Comparative Example 1 and Example 1 is that the modified chitosan zinc oxide is replaced by an equal amount of rod-shaped nano zinc oxide particles, so the rod-shaped nano zinc oxide is not modified by chitosan cinnamaldehyde Schiff base and silane. As can be seen from Table 2, the antibacterial rate of Comparative Example 1 is significantly reduced, only 85.0%, while Example 1 reaches 99.5%. This shows that the unmodified zinc oxide particles have poor dispersibility and insufficient binding ability with the polyester matrix, resulting in a decrease in antibacterial effect. At the same time, the mechanical properties are slightly reduced (16.0cN / tex), and the air permeability is also reduced from 320mL / cm in Example 1. 2 ·s dropped to 310mL / cm 2 ·s, which may be due to the uneven dispersion of particles, resulting in a certain influence on the fiber pore structure.
[0122] The main difference between Comparative Example 2 and Example 1 is that the same amount of rod-shaped nano zinc oxide particles are not treated with silane modification. As can be seen from Table 2, the antibacterial rate of Comparative Example 2 is slightly improved (91.0%), but it is still significantly lower than the 99.5% of Example 1. This is because although the rod-shaped nano zinc oxide has a good morphology, the lack of silane modification will lead to insufficient surface activity of the particles and weak interface interaction with the fiber matrix, affecting the release efficiency of the antibacterial substance. In addition, the mechanical properties (15.8 cN / tex) and air permeability (318 mL / cm 2 ·s) are slightly lower than those in Example 1, indicating that the interfacial properties of the particles have a certain influence on the comprehensive properties of the yarn.
[0123] The main difference between Comparative Example 3 and Example 1 is that commercial nano zinc oxide particles (spherical) are used to replace rod-shaped nano zinc oxide particles. As can be seen from Table 2, the antibacterial rate of Comparative Example 3 is significantly reduced, only 80.0%, which is much lower than 99.5% of Example 1. This is because the commercial spherical particles have a smaller specific surface area, fewer active sites, and a significantly reduced antibacterial effect. The mechanical properties (15.5cN / tex) also decreased, which may be due to the weaker enhancement effect of the spherical particles on the fiber cohesion. At the same time, the air permeability decreased significantly, only 290mL / cm 2 ·s, which indicates that the spherical particles may affect the pore distribution between fibers and hinder air circulation.
[0124] The main difference between Comparative Example 4 and Example 1 is that POE elastomer is not added when preparing the polyester fiber. As can be seen from Table 2, the antibacterial rate of Comparative Example 4 (98.5%) is close to 99.5% of Example 1, indicating that the absence of POE elastomer has little effect on the antibacterial performance. However, the mechanical properties (16.0 cN / tex) are slightly lower than 16.2 cN / tex of Example 1, because POE elastomer can enhance the flexibility and tensile strength of the fiber. The air permeability is similar to that of Example 1, which is 315 mL / cm 2·s, indicating that POE elastomer has limited effect on the air permeability of the fiber.
[0125] The main difference between Comparative Example 5 and Example 1 is that no polyether-modified silicone oil was added when preparing the polyester fiber. As can be seen from Table 2, the antibacterial rate of Comparative Example 5 (98.0%) is slightly lower than that of Example 1 (99.5%), indicating that the absence of polyether-modified silicone oil has a certain influence on the antibacterial performance, probably because the uniform coating formed on the fiber surface helps the distribution and release of antibacterial substances. The mechanical properties (15.8 cN / tex) are slightly lower than those of Example 1, indicating that the lubricating effect of silicone oil has a certain contribution to the fiber strength. The air permeability is significantly reduced to only 280 mL / cm 2 ·s, which may be because the lack of silicone oil reduces the smoothness of the fiber surface and affects the air flow.
[0126] The main difference between Comparative Example 6 and Example 1 is that POE elastomer is not added when preparing the polyester fiber. As can be seen from Table 2, the antibacterial rate of Comparative Example 6 (97.0%) is lower than 99.5% of Example 1, indicating that the absence of POE elastomer may indirectly affect the uniform distribution of antibacterial substances. The mechanical properties (15.8 cN / tex) are significantly lower than those of Example 1, because POE elastomer can improve the flexibility and strength of the fiber. Air permeability (312 mL / cm 2 ·s) is slightly lower than 320mL / cm in Example 1 2 ·s, but still higher than some comparative examples, indicating that it has little effect on the fiber pore structure.
[0127] In summary, by comparing the performance of Examples 1 to 4 and Comparative Examples 1 to 6, it can be seen that the synergy of component design has a crucial impact on the comprehensive performance of yarn and antibacterial breathable socks. The introduction of modified chitosan zinc oxide significantly improves the antibacterial rate under the synergistic modification of chitosan cinnamaldehyde Schiff base and silane, ensuring the durability and stability of the antibacterial effect; while zinc oxide particles that are not modified or replaced with other morphologies will weaken the dispersibility and interfacial action of the antibacterial agent, resulting in a significant decrease in antibacterial performance. In addition, the addition of POE elastomers and polyether-modified silicone oils plays a key role in the mechanical properties and air permeability of the yarn, respectively, and both form a good synergistic effect in improving fiber flexibility, strength and air circulation. In particular, the presence of POE elastomers not only enhances the breaking strength of the fiber, but also improves the wearing comfort and durability of the yarn to a certain extent. These results show that the excellent performance of yarn and socks is not the effect of a single component, but the result of the mutual synergy of the components in chemical modification, physical dispersion and performance reinforcement. Reasonable component design and optimization can achieve a balance between hygroscopicity, mechanical properties, breathability and antibacterial properties, ultimately giving the product excellent comprehensive performance and meeting multifunctional needs.
[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. An antibacterial breathable yarn, characterized in that: The antibacterial breathable yarn is obtained by spinning polyester fiber, nylon fiber, cotton fiber and elastic fiber; The mass ratio of the polyester fiber, nylon fiber, cotton fiber and elastic fiber is (40-60):(20-30):(10-20):(5-10); The polyester fiber is prepared from the following components in parts by weight: 85-90 parts of polyethylene terephthalate chips, 3.0-5.0 parts of modified chitosan zinc oxide, 0.3-0.5 parts of antioxidant 1010, 1.0-2.0 parts of POE elastomer, 2.0-3.0 parts of polyether modified silicone oil, and 1.0-2.0 parts of polyethylene glycol 200; The modified chitosan zinc oxide is prepared by combining chitosan cinnamaldehyde Schiff base and silane-modified zinc oxide; The chitosan cinnamaldehyde Schiff base is obtained by a Schiff base condensation reaction of chitosan and cinnamaldehyde in acetic acid and anhydrous ethanol medium; The silane-modified zinc oxide is isocyanate propyltriethoxysilane-modified nanorod-shaped zinc oxide particles.
2. The antibacterial breathable yarn according to claim 1, characterized in that: The preparation method of the modified chitosan zinc oxide is as follows: by weight, 10.0-15.0 parts of chitosan cinnamaldehyde Schiff base are added to 500-600 parts of deionized water, and then the pH of the mixed solution is adjusted to 3.0-4.0 with a 3.0wt.% acetic acid solution, and after the adjustment, the solution is stirred at 60-70°C at a stirring rate of 200-250rpm for 20-30min, and then 40.0-50.0 parts of silane-modified zinc oxide are added to the solution, and the mixed solution is placed in an ultrasonic device. The method comprises the following steps: firstly subjecting the mixture to ultrasonic treatment for 20 to 30 minutes, and then stirring the mixture in a water bath at 50 to 60° C. for 30 to 45 minutes. After the stirring, the pH value of the mixed solution is adjusted to 8.8 to 9.2 with a 5wt.% sodium hydroxide solution. After the adjustment, a flocculent precipitate is formed in the mixed solution. Then, the mixed solution is filtered and the precipitate is retained. The precipitate is washed with deionized water for 3 times. After the washing, the precipitate is dried in a vacuum drying oven at 50 to 60° C. for 8 to 12 hours. The dried product is ground into a particle size of 200 meshes to obtain modified chitosan zinc oxide.
3. An antibacterial breathable yarn as claimed in claim 1 or 2, characterized in that: The preparation method of the silane-modified zinc oxide is as follows: by weight, 15.0-20.0 parts of ethyl glycolate and 40.0-50.0 parts of isocyanatepropyl triethoxysilane are added to a beaker, and 0.20-0.40 parts of dibutyltin dilaurate are added, and the mixture is stirred at 40.0-45.0° C. and a stirring rate of 300-350 rpm for 200-240 minutes to form a uniform mixed solution, and then 100-150 parts of nanorod-shaped zinc oxide particles, 200-250 parts of anhydrous ethanol and 150-160 parts of deionized water are added to the mixed solution in sequence. Then the mixed solution is ultrasonicated for 30 to 45 minutes. After the ultrasonic treatment is completed, the pH value of the solution is adjusted to 9.8 to 10.2 with a 5wt.% sodium hydroxide solution. After the pH value is adjusted, the mixed solution is stirred in a water area of 60 to 65° C. at a stirring rate of 300 to 400 rpm for 240 to 300 minutes. After the stirring is completed, the mixed solution is filtered and the precipitate is retained. Then, the precipitate is washed alternately with deionized water and anhydrous ethanol for 3 to 5 times, and the washed precipitate is dried at 50 to 60° C. for 6 to 10 hours to obtain silane-modified zinc oxide.
4. The antibacterial breathable yarn according to claim 3, characterized in that: The preparation method of the chitosan cinnamaldehyde Schiff base is as follows: by weight, 10.0-15.0 parts of chitosan are dissolved in 100-120 parts of 1wt.% acetic acid solution to obtain a chitosan solution, and 7.0-10.0 parts of cinnamaldehyde are dissolved in 300-400 parts of anhydrous ethanol to obtain a cinnamaldehyde solution, and then the cinnamaldehyde solution is added dropwise to the chitosan solution. After the dropwise addition is completed, the mixed solution is placed in an oil bath at 40-50°C and stirred at a stirring rate of 350-400rpm. The mixture was stirred for 300 to 360 minutes, and after the stirring was completed, a 5 wt.% sodium hydroxide solution was slowly added dropwise to the solution, and the pH of the solution was adjusted to 10, until a flocculent precipitate was formed in the solution, and then the mixed solution was filtered and the precipitate was retained, and the obtained precipitate was washed alternately with anhydrous ethanol and deionized water for 3 times, and then the precipitate was transferred to a vacuum drying oven and dried at 50 to 60° C. for 200 to 240 minutes. The dried product was ground to a particle size of 200 mesh to obtain a yellow powder of chitosan cinnamaldehyde Schiff base.
5. The antibacterial breathable yarn according to claim 1, characterized in that: The preparation method of the polyester fiber is as follows: polyethylene terephthalate chips, antioxidant 1010 and POE elastomer are added to a high-speed mixer, mixed at 300-500 rpm for 5-10 minutes at room temperature to obtain uniformly dispersed raw materials, then the uniformly dispersed filler is added to a twin-screw blending extruder, melt blended at 250-280°C for 30-45 minutes, and the melt blending rate is 300-500 rpm. During the blending process, modified chitosan zinc oxide and polyether modified silicone oil are gradually added thereto, and then a fiber masterbatch is obtained by extrusion, and then the fiber masterbatch is added to a melt spinning device, and spun at 260-280°C to form polyester fibers.
6. The antibacterial breathable yarn according to claim 3, characterized in that: The preparation method of the nano-rod-shaped zinc oxide particles is as follows: by weight, 0.5-1.0 parts of zinc nitrate and 0.5-1.0 parts of urea are dissolved in 100-200 parts of deionized water, and stirred at a stirring rate of 300-500 rpm for 10-20 minutes to form a mixed solution; the mixed solution is transferred to a hydrothermal reaction kettle, sealed, reacted at 90-95° C. for 240-360 minutes, cooled naturally to room temperature after the reaction is completed, the reaction solution is filtered and solid powder is retained, and the solid powder is washed with deionized water for 3-5 times, each washing time is 5-10 minutes, and the washed solid powder is placed in a vacuum drying oven at 50-60° C. for 6-10 hours to obtain nano-rod-shaped zinc oxide particles.
7. The antibacterial breathable yarn according to claim 6, characterized in that: The average diameter of the nanorod-shaped zinc oxide particles is 50-100 nm, and the average length is 500-1000 nm.
8. The antibacterial breathable yarn according to claim 1, characterized in that: The preparation method of the antibacterial breathable yarn is as follows: polyester fiber, nylon fiber, cotton fiber and elastic fiber are spun by air-spinning, the spinning tension is set to 8-15 cN, the twist is 300-500 twists / m, and the spinning speed is 100-200 m / min; the spun yarn is drafted, the draft ratio is controlled at 1.2, and then twisted, the twist coefficient is controlled at 3.5-4.5, and the yarn is wound into a tube, and the winding tension is controlled at 5-10 cN, so as to prepare the antibacterial breathable yarn; The elastic fiber is Lycra fiber or spandex fiber. 9.An antibacterial breathable socks, characterized in that The antibacterial breathable socks are woven using the antibacterial breathable yarn according to any one of claims 1 to 8; The preparation method of the antibacterial breathable socks is as follows: using the antibacterial breathable yarn, knitting the socks through a knitting machine according to the sock weaving design requirements, the needle pitch of the knitting machine is 12 to 18 needles / inch, the weaving tension is 5 to 15 cN, and the weaving speed is 20 to 40 rpm; the knitting density is adjusted according to the functional requirements of different parts of the socks, wherein the knitting density of the sock bottom is appropriately reduced, the knitting density is controlled at 150 to 180 needles / square inch to enhance the air permeability, and the knitting density of the sock opening is appropriately increased. The knitting density is controlled at 200 to 240 needles per square inch to improve elasticity and fit; after knitting, the socks are sewed, the sewed process adopts a chain stitch method, and the sewing thread tension is controlled at 4 to 8 cN, and then the socks are shaped, the shaping temperature is 80 to 100° C., and the shaping time is 3 to 8 minutes; the shaped socks are heat-set, the heat-setting temperature is 120 to 150° C., and the setting time is 5 to 15 minutes; finally, antibacterial and breathable socks are prepared.
Citation Information
Patent Citations
Yarn
CN104611798A
Antibacterial fiber yarn
CN107299437A
Cinnamaldehyde crosslinked chitosan drug-loading microsphere preparation method
CN104138356A
Mildew preventive special for bamboo
CN108943256A
Carboxylated chitosan hollow yarn and preparation method thereof
CN115287799A
Cited By
Antibacterial environment-friendly dyed fiber and preparation method thereof
CN120231149A
Preparation method of superfine antibacterial fiber
CN120683626A
Nano-composite antibacterial mildew-proof polyester fiber and preparation method thereof
CN120719416A
Cool antibacterial polyester fabric and preparation method thereof
CN121538757A
Antibacterial printed silk fabric and preparation method thereof
CN121611002A